Legal Protection Concerning Domestic Flights Passengers of Air Transport Services - Sudiarto Sudiarto; Budi Sutrisno (Faculty of Law, University of Mataram, 2020)
The aims of this paper is to discuss and analyze the legal protection concerning air transport consumers on domestic flights. The method using normative method with statute approach and conceptual approach. The results of this paper is to discuss the particular regulations on special facilities for disabilities, elderly, children under the age of 12 years and the patient are not found under the domestic flights regulation in Indonesia. The procedure in obtaining compensation to passengers who passed away because of the aircraft accident is extremely complicated. In addition, the compensation to passengers caused by the flight delays have not been optimally implemented.